Ag-Bridged Z‑Scheme 2D/2D Bi5FeTi3O15/g-C3N4 Heterojunction for Enhanced Photocatalysis: Mediator-Induced Interfacial Charge Transfer and Mechanism Insights - Wang, Kai; Li, Jun; Zhang, Gaoke (ACS applied materials & interfaces, 2019)
Heterojunction photocatalysts have attracted widespread interest in photocatalysis because of their high-efficiency interfacial charge-transfer characteristics of nanoarchitectures. In this study, Ag-bridged 2D/2D Bi5FeTi3O15/ultrathin g-C3N4 Z-scheme heterojunction photocatalysts with powerful interfacial charge transfer has been synthesized via a facile ultrasound method coupled with a photoreduction strategy for efficient photocatalytic degradation of antibiotics. The morphology analysis displays that the bridged Ag nanoparticles were anchored on the interface of layered Bi5FeTi3O15 and ultrathin g-C3N4 nanosheets. Owing to its unique 2D/2D ternary heterostructure, the Bi5FeTi3O15/2%Ag/10% ultrathin g-C3N4 composite exhibited the best tetracycline degradation performance under visible-light and simulated solar irradiation. Meanwhile, the intermediates and degradation pathways were proposed by a liquid-phase mass spectrometry system. Characterizations and density functional theory studies together verify that the matched band structure of Bi5FeTi3O15 and g-C3N4 could induce a superfast Z-scheme interfacial charge-transfer path. More importantly, bridged Ag nanoparticles in the 2D/2D heterojunction extended the light absorption range and prolonged the lifetime of photogenerated electron–holes induced by Bi5FeTi3O15. This work affords a promising approach for designing multicomponent Z-scheme heterojunction photocatalysts for highly efficient photocatalytic application.